Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/1742-6596/753/3/032020
|View full text |Cite
|
Sign up to set email alerts
|

Wake effects between two neighbouring wind farms

Abstract: Wake effect on a uniform flow behind wind-turbine model V L Okulov, I V Naumov, R F Mikkelsen et al.Simulation of wake effects between two wind farms K S Hansen, P-E Réthoré, J Palma et al. Abstract. We address the issue of wake effects between two neighbouring offshore wind farms by analysing simultaneous production data from Rødsand II and Nysted. The upstream wind farm is found to not just perturb the flow in its wake, but also to cause speed-ups at the positions of some downstream turbines. We use the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 9 publications
3
44
0
Order By: Relevance
“…Most offshore observational studies have so far generally focused on the wind and power deficit observed in and downwind of large wind farms (e.g. Barthelmie et al 2010, Nygaard 2014, Nygaard and Hansen 2016 except Foreman et al (2017). Only few studies have investigated the potential effect of wind Original content from this work may be used under the terms of the Creative Commons Attribution 3.0 licence.…”
Section: Introductionmentioning
confidence: 99%
“…Most offshore observational studies have so far generally focused on the wind and power deficit observed in and downwind of large wind farms (e.g. Barthelmie et al 2010, Nygaard 2014, Nygaard and Hansen 2016 except Foreman et al (2017). Only few studies have investigated the potential effect of wind Original content from this work may be used under the terms of the Creative Commons Attribution 3.0 licence.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of wake effects around large offshore wind farms are focused on wake interaction within the wind farms or between closely adjacent wind farms (Barthelmie et al, 2010;Hansen et al, 2012Hansen et al, , 2015Nygaard 2014;Volker et al, 2015;Nygaard and Hansen 2016). Investigations of wind farm wake effects based on SAR wind maps have revealed the existence of extensive wakes under certain atmospheric conditions (Christiansen and Hasager 2005;Christiansen et al, 2006;Li and Lehner 2013;Hasager et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Good results are obtained in the open sea but in coastal regions near upstream land mass the uncertainty increases . Wind farm wakes are not simulated by NWP models unless the effect of wind turbines to the atmospheric flow are parameterized (Fitch et al, 2012;Volker et al, 2015) Engineering wind farm models like the Park model (Jensen, 1983), Fuga (Ott et al, 2011), and the Gunnar C. Larsen model (Larsen, 2009) have been used in combination with WRF outputs (Peña et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For offshore wind farms, wakes are responsible for the largest single loss of energy production. Considerable effort is therefore being put to the analysis and modelling of wake effects [1][2][3][4][5][6][7][8][9]. Normally, the wakes are invisible, discernible only through the reduced production of downstream turbines caught in the wakes.…”
Section: Introductionmentioning
confidence: 99%